InteraHeu: Heuristics for technological interaction on events - Gomes, Genildo; de Freitas, Rosiane; Castro, Thais; Gadelha, Bruno (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2020)
The use of technologies to promote public interaction at different types of events is increasingly popular. Actions range from lighting smartphone flashes at concerts and festivals to interactive polls at lectures and scientific events. All of this represents attempts to appropriate the technology that is already part of people’s daily lives to facilitate a more active public participation. Based on the techniques of audience engagement and collaborative interaction, this research aims to classify and systematize the characteristics of the most varied events involving the participation of people, aiming at their technology-mediated active participation. Thus, this paper discusses the characteristics and technological insertion proposed in some real events, sources of experimental studies, and, consequently, heuristics for technological insertion for interaction in these and other events.